Helicobacter pylori first‐line and rescue treatments in patients allergic to penicillin: Experience from the European Registry on H pylori management (Hp‐EuReg). Issue 3 (16th March 2020) - Nyssen, Olga P.; Pérez‐Aisa, Ángeles; Tepes, Bojan; Rodrigo‐Sáez, Luis; Romero, Pilar M.; Lucendo, Alfredo; Castro‐Fernández, Manuel; Phull, Perminder; Barrio, Jesús; Bujanda, Luis; Ortuño, Juan; Areia, Miguel; et al.
Abstract: Background: Experience in Helicobacter pylori eradication treatment of patients allergic to penicillin is very scarce. A triple combination with a PPI, clarithromycin (C), and metronidazole (M) is often prescribed as the first option, although more recently the use of a quadruple therapy with PPI, bismuth (B), tetracycline (T), and M has been recommended. Aim: To evaluate the efficacy and safety of first‐line and rescue treatments in patients allergic to penicillin in the "European Registry of H pylori management" (Hp‐EuReg). Methods: A systematic prospective registry of the clinical practice of European gastroenterologists (27 countries, 300 investigators) on the management of H pylori infection. An e‐CRF was created on AEG‐REDCap. Patients with penicillin allergy were analyzed until June 2019. Results: One‐thousand eighty‐four patients allergic to penicillin were analyzed. The most frequently prescribed first‐line treatments were as follows: PPI + C + M (n = 285) and PPI + B + T + M (classic or Pylera ® ; n = 250). In first line, the efficacy of PPI + C + M was 69%, while PPI + B + T + M reached 91% ( P  < .001). In second line, after the failure of PPI + C + M, two rescue options showed similar efficacy: PPI + B + T + M (78%) and PPI + C + levofloxacin (L) (71%) ( P  > .05). In third line, after the failure of PPI + C + M and PPI + C + L, PPI + B + T + M was successful in 75% of cases. Conclusion: In patients allergic to penicillin, a triple combination with PPI + C + M should not be generally recommended as a first‐line treatment, while a quadruple regimen with PPI + B + T + M seems to be a better option. As a rescue treatment, this quadruple regimen (if not previously prescribed) or a triple regimen with PPI + C + L could be used but achieved suboptimal (<80%) results.